2022
DOI: 10.1186/s12916-022-02458-2
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective database study of the demographic features and glycemic control of patients with type 2 diabetes in Kinshasa, Democratic Republic of the Congo

Abstract: Background The Kin-Antwerp project aimed at improving the quality of care provided to patients with diabetes in Kinshasa, the Democratic Republic of the Congo in Central Africa, including the digitalisation of routine clinical data to improve patients’ follow-up. We aim to analyse the data of a study population of Kin-Antwerp to characterise their demographic features, assess their achievement of glycemic target over time, and identify groups requiring prioritised attention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Female patients represented approximately two-thirds of the participants. A retrospective analysis of the Kinshasa Health Network database conducted by Sagastume et al 11 also found the same-sex prevalence. This high prevalence of type 2 diabetes affects more women than men, due to the higher metabolic risk in the former.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Female patients represented approximately two-thirds of the participants. A retrospective analysis of the Kinshasa Health Network database conducted by Sagastume et al 11 also found the same-sex prevalence. This high prevalence of type 2 diabetes affects more women than men, due to the higher metabolic risk in the former.…”
Section: Discussionmentioning
confidence: 82%
“…9 In the DRC, very few studies have investigated poor glycaemic control among persons/patients living with type 2 diabetes, as high as 86% in the nearby province of Kwilu 10 and 79.9% in Kinshasa. 11 Only a few reported factors were found to be associated with glycaemic control among persons living with type 2 diabetes mellitus in the DRC. Sagastume et al 11 This study aimed to assess the extent of glycaemic control and to broaden the knowledge on factors driving poor glycaemic control among patients living with type 2 diabetes in Kinshasa.…”
Section: Intrdoductionmentioning
confidence: 99%
See 3 more Smart Citations